SUSTAINABLE WORK-LIFE INTEGRATION POST-PANDEMIC: COPING AND RESILIENCE STRATEGIES IMPACTING JOB PERFORMANCE - Mrs. K.Sangeetha and Dr.Vanathi Vembar (South Eastern European Journal of Public Health, 2025)
The COVID-19 pandemic highlighted major challenges in balancing work and family responsibilities, stressing the importance for business to embrace and apply strong coping and resilience measures. The purpose of this study is to examine how IT employers can boost job performance and support work-family equilibrium in the post-pandemic context, while improving employee well-being and productivity. This study seeks ways to build resilience through coping strategies and organizational support by using both qualitative interviews and quantitative surveys with IT workers. The initial results indicate that clear communication, employee support programs, and flexible work options is required for solving work-family problems and boosting job performance. To improve resilience and productivity, the study suggests that employers focus on offering flexible work arrangements, mental health support, and fostering a positive work culture.